Lao Fabric Weaving Business in Luangprabang Capital City - PHAIGNAVONG, Somchay; SIRISACK , Dalyvanh; CHANTHAMANIVONG, Keo (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The objectives of this research were to study: 1) the Lao fabric weaving business in Luangprabang Capital City; 2) factors influencing to the Lao fabric weaving business in Luangprabang Capital City. It was a quantitative research using interviewing forms as tools for data collecting from 120 people producing Lao fabric weaving business in 2 villages: Ban Pha Nom and Ban Chang Kong in Luangprabang Capital City. To data analyze: for a single variable, statistics used consisted of percentage, mean, standard deviation, minimum and maximum values; for two variables, Chi-square was used; and for multi-variables, regression multiple was used by Enter method. The research outcome appeared: most of the Lao fabric weaving in production, accounted for 57,9%, while those having highest roles accounted 16,3%. It was also found the people on production operating, accounted 86,6%, followed byones people on production planning accounted 81,2% and marketing, accounted 73,8% respectively. As of the factors influencing to Lao fabric weaving business statistically significant at 0,01 and 0,05 were ages, income, operation fund, social support, and the expected benefit from Lao fabric weaving as related by 0,129, 0,200, 0,351,0,241 and 0,230 respectively.